2002
DOI: 10.1038/sj.gene.6363869
|View full text |Cite
|
Sign up to set email alerts
|

A CTLA-4 gene polymorphism at position −318 in the promoter region affects the expression of protein

Abstract: Sweden CTLA-4 is an important negative regulator of the immune system. The regulation of the CTLA-4 gene (Ctla-4) transcription is poorly understood. A single nucleotide polymorphism (SNP) at −318 in the Ctla-4 promoter region is associated with certain autoimmune diseases. Since the −318 SNP occurs in a potential regulatory region, it is conceivable that the CЈ T transition may affect the expression of In the present study, we show that the −318T allele is associated with a higher promoter activity than the −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
129
3
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(141 citation statements)
references
References 6 publications
6
129
3
2
Order By: Relevance
“…This SNP is the only one of the CTLA4 5 0 -flanking SNPs that is located in a phylogenetically conserved region and its undertransmitted T allele (frequency ¼ 0.09) is predicted to disrupt a response element for TCF1/LEF1, a pair of transcription factors important in lymphocyte development. 7 We found that this genetic effect is independent of the þ 6230 SNP and we confirmed a previous report 8 of increased in vitro transcription of the À318T allele. 9 This transcriptional effect is relevant in vivo as we showed that, in heterozygous subjects, there was increased CTLA4 mRNA transcribed from the T allele, 9 an effect we hypothesized may be mediated by the disruption of the predicted TCF1/LEF1 site.…”
Section: Introductionsupporting
confidence: 91%
“…This SNP is the only one of the CTLA4 5 0 -flanking SNPs that is located in a phylogenetically conserved region and its undertransmitted T allele (frequency ¼ 0.09) is predicted to disrupt a response element for TCF1/LEF1, a pair of transcription factors important in lymphocyte development. 7 We found that this genetic effect is independent of the þ 6230 SNP and we confirmed a previous report 8 of increased in vitro transcription of the À318T allele. 9 This transcriptional effect is relevant in vivo as we showed that, in heterozygous subjects, there was increased CTLA4 mRNA transcribed from the T allele, 9 an effect we hypothesized may be mediated by the disruption of the predicted TCF1/LEF1 site.…”
Section: Introductionsupporting
confidence: 91%
“…In this regard, an association between CTLA-4 promoter genotypes at position À318 and levels of CTLA-4 molecule has been demonstrated. 25,26 However, the two variants of this SNP were not predicted to be a binding site for homo sapiens transcription factors (http://mbs.cbrc.jp/research/db/TFSEARCH.html). Alternatively, the associations observed here might Association of CTLA-4 gene promoter polymorphisms S Almasi et al be related to linkage disequilibrium between the CTLA-4 alleles at these positions and those of a putative locus for SSc.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 The human CTLA4 gene is known to contain polymorphisms in three distinct regions: a C4T single-base substitution in the promoter at position À318, an A/G dimorphism in exon 1 at position 49, and a multiallelic dinucleotide repeat in the 3¢ untranslated region. 12,31,32 When we screened the four coding exons and the promoter of the CTLA gene for genetic variability in DCM patients and healthy controls, we confirmed the presence of known SNPs in the promoter and in exon 1. We observed that the allelic distribution of the promoter SNP was not associated with the prevalence of DCM.…”
Section: Ctla4 Receptor In the Pathogenesis Of Dcmmentioning
confidence: 78%